CAPACITY BUILDING AND STRATEGY: VOCATIONAL AND STRATEGIC TRAINING CAPACITY BUILDING AND KNOWLEDGE II A PEKAN BARU - Rezi Nalsal; Padmono Wibowo (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes vocational training strategies as an effort to empower inmates at the Class IIA Pekanbaru Correctional Institution and identifies the factors that support and hinder their implementation. Using a qualitative approach, data were collected through interviews, observations, and documentation, and analyzed thematically. The study applies the Management by Objectives (MBO) and Empowerment Theory frameworks to understand how empowerment strategies are carried out. The findings show that the empowerment strategy is participatory and humanistic, where inmates are involved in training based on their interests, such as animal husbandry, agriculture, and barista skills. The training combines theory and practice, emphasizes independence, and builds trust in inmates to develop their abilities. This approach helps inmates gain useful skills and prepares them for reintegration into society. However, the program still faces several obstacles, making it necessary to strengthen collaboration among stakeholders. With better cooperation and support, the institution can optimize the potential of inmates most of whom are of productive age and support the realization of independent and socially reintegrated individuals in line with correctional system goals. Keywords: Vocational Training; Correctional Inmates; Lapas Class IIA Pekanbaru; Development Strategy; Social Reintegration